Annular flow stability within small-sized channels. (January 2018) - Giannetti, Niccolò; Kunita, Daisuke; Yamaguchi, Seiichi; Saito, Kiyoshi
Highlights: Surface tension effects on the flow stability were studied within small-sized channels. The equilibrium transition line of the annular regime was theoretically drawn. The stable void fraction and interfacial extension of the flow were identified. A higher surface tension is responsible for a lower void fraction and higher slip ratio. The results from previous literature were obtained as a limiting case of this model. Abstract: An analytical study based on a variational thermodynamic principle is presented to evaluate the influence of surface tension on the stability of annular flow within small-sized channels. The model introduces phenomenological assumptions in the interfacial structure of the flow regime and theoretically draws the equilibrium transition line from an annular regime to the initiation of the partial wetting condition on the inner surface. By including surface tension, this model expands previous theories and identifies the stable flow configuration in terms of void fraction and interfacial extension. The significant influence of a higher surface tension and smaller diameter (i.e. lower Weber number) are responsible for a lower stable void fraction and higher slip ratio. A complete screening of the main influential parameters is conducted to explore the descriptive ability of the model. This analysis aims at contributing to the understanding of the stability of two-phase flow regimes and can be extended to the transition between other neighbouring regimes, including wall friction as well as liquid entrainment phenomena.